Natural organic matter dynamics in permafrost peatlands: critical overview of recent findings and characterization tools - Folhas, Diogo (2025)
Rising temperatures are destabilizing permafrost in northern latitudes, leading to the mobilization, transformation and cycling of natural organic matter (NOM), nutrients, and contaminants into newly formed aquatic systems. Analyzing the chemical composition of organic matter is crucial for understanding the biogeochemical processes at play. Furthermore, it is essential to investigate how seasonal variations and anoxic conditions influence these processes, as well as their effects on microbial activity and NOM composition. This review provides an overview of northern peatlands, terminal electron acceptor species, and key analytical techniques used to characterize organic matter: UV/Vis and Fluorescence Spectroscopy, FTIR, FT-ICR-MS, and Nuclear Magnetic Resonance. Rather than focusing on the theoretical aspects of these techniques, we emphasize the type of information they offer about NOM and how to interpret these data within the context of biogeochemical transformations in permafrost-affected systems.